Experimental long bone fracture healing in goats with cockle shell-based calcium carbonate bone paste - Saroj Kumar Yadav; Subrata Kumar Shil; Monoar Sayeed Pallab; Kh. Nurul Islam; Bibek Chandra Sutradhar; Bhajan Chandra Das (Veterinary and Animal Science, 2024)
Long bone fractures are common orthopedic conditions. There are numerous ways to repair these fractures. Bone grafting becomes necessary when a broken bone has a significant gap. However, due to insufficient donor volume and donor site morbidity, substitutes are required. In veterinary orthopaedics, calcium carbonate from cockle shells could be used as a bone biomaterial. We investigated its efficacy as a bone biomaterial repair for goat femoral fractures. The study included 10 healthy adult male Black Bengal goats weighing 8 kg and aged 12–13 months. The study includes control and treatment groups. Intramedullary pinning stabilized an 8-mm right femur diaphyseal fracture in the treatment and control groups. The treated group received 2 ml of bone paste in the fractured gap, whereas the control group left it empty. We examined all goats with X-rays on the 7th, 45th, and 60th days, followed by gross and histological findings. Due to callus bridging, radiographs revealed faster bone growth in the treated group than in the control group. Gross examination demonstrates the treated group had a larger fracture callus than the control group. Histopathology showed that bone formed faster and included more osteocytes, osteoblasts, osteoclasts, and bony spicules than in the control group. The treated group had more periosteum osteoblasts, while the control group had fibroblasts. These results showed that the treated group had more osteogenic activity than the control group. This study demonstrates the potential of cockle shell-based calcium carbonate bone paste as a synthetic biomaterial for healing long bone fractures in goats.